Application of Graphene as a Sorbent for Preconcentration and Determination of Trace Amounts of Lead in Water Samples Prior to Flame Atomic Absorption Spectrometry - Dong, Yan-Li; Liu, Qi-Feng; Zhou, Xin; Tao Gao, Shu; Ci Li, Jing; Jun Ma, Jing (Asian Journal of Chemistry, 2013)
Graphene, a novel class of carbon nanostructures, has great promise for use as sorbent materials because of its ultrahigh specific surface area. A new method using a column packed with graphene as sorbent was developed for the preconcentration of trace amounts of lead prior to its determination by flame atomic absorption spectrometry. Under the optimal conditions, the calibration graph was linear in the concentration range of 10-600 μg L-1 with a detection limit of 0.54 μg L-1. The relative standard deviation for ten replicate measurements of 400 μg L-1 of Pb was 3.33 %. This proposed method was successfully applied to tap water, river water and sea water and accuracy was assessed through the analysis of certified reference water or recovery experiments.